Arduino-Based Air Pipe Leak Detection System - Ari Alriawan; Zulfikar Zulfikar (NEWTON: Networking and Information Technology, 2025)
Leakage in water pipelines can lead to significant losses both economically and environmentally. To address this issue, this study presents the design and implementation of a leakage detection system using the Arduino Nano microcontroller and YF-S201 flow sensors. The system works by comparing water flow data at two points in the pipeline. If there is a significant difference in flow rate, the system detects it as a leak and activates a buzzer as an alarm while displaying information on an LCD 16x2 I2C. Testing results showed that the system is able to accurately detect leaks with an average delay of less than 1 second.